Segmentation, Targeting, Positioning (STP), Communication and Price Strategies on Consumer Purchasing Decisions at PT. Alfa Scorpii Medan - Calvin Bigo; Arvin Raj; Rosinta Romauli Situmeang (Jurnal Mantik, 2021)
This study aims to determine the effect of segmentation, targeting, positioning, communication and price towards purchase decisions. This type of research is explanatory research. The entire population is 9.408consumer. Due to a large population, the sampling technique will be reduced by using the Slovin formula with an error tolerance level of 10% so that there are as many as 99 respondents in the study which will be distributed with questionnaires measured by a Likert scale. The data analysis used multiple linear regression analysis, and the coefficient of determination as well as simultaneous test, and partial test. The results showed that segmentation, targeting, positioning, communication and price partially, andsimultaneously have a positive, and significant effect on purchase decision. Based on the results of this study, the implications for management are to further improve the better segmentation, targeting, positioning, communication and price.